Digital Support for Succession in a Family Business - Repas, Ana; Marič, Miha (Izzivi prenosa vodenja na naslednjo generacijo v družinskem podjetju, 2025)
Succession in family businesses is a complex process that extends beyond the formal transfer of ownership or leadership roles. It encompasses the transmission of knowledge, values, and the company’s long-term vision. In the digital era, technological support is gaining importance by enabling transparency, efficiency, and strategic continuity. Despite these opportunities, digital transformation also introduces challenges, particularly in adapting modern technologies to traditional family business environments. This chapter explores the role of digital tools in one of the most sensitive stages of family business development – transferring leadership to the next generation. The empirical section is based on an in-depth interview with the deputy director of DINES d.o.o., Domen Deu. The analysis focuses on leadership transfer, digital tool usage, and preserving organizational knowledge. Findings reveal that, following the appointment of a new manager, the company gradually began introducing digital solutions, while formal ownership transfer is still ongoing. Based on these insights, proposals for improvement include establishing a digital knowledge management platform and enhancing digital skills across all employee generations.